From Indifference to Hostility: Police Officers, Organizational Responses and the Symbolic Value of 'in-Service' Higher Education in Policing. (31st January 2017) - Hallenberg, Katja M.; Cockcroft, Tom
Abstract: The relationship between Higher Education (HE) and the knowledge and skill requirements of police officers remains a contentious policy area in England. This paper addresses experiences of 31 officers from a large urban force who have undertaken HE level study whilst in service. Overwhelmingly, officers reported a sense of indifference on the part of the organisation to their successful completion of an HE level educational programme. In addition, some participants experienced tokenistic acknowledgement of their achievement whilst others perceived outright hostility. In light of the findings we argue that, for the police organisation, there is a danger that the value of HE appears in its symbolic cultural capital rather than in the substantive knowledge and skills graduate officers could bring to the organisation and practice of policing. Moreover, the lack of structural and cultural integration has a detrimental effect on how officers with in-service degrees view their work, career prospects and the organisation as a whole.